Spontaneous rip of the retinal pigment epithelium with a macular hole in neovascular age-related aacular degeneration - Emerson, Geoffrey G. (2005)
Purpose To report a case of retinal pigment epithelial tear associated with a macular hole in a patient with neovascular age-related macular degeneration (AMD). Design Observational case report. Methods An 87-year-old woman with AMD-related fibrovascular pigment epithelial detachment associated with vision loss was followed with sequential fundus photography, fluorescein angiography, and optical coherence tomography for 8 months. Results The detachment developed into a retinal pigment epithelium tear with macular hole formation. The temporal evolution of the lesion and optical coherence tomography findings suggested that the retinal pigment epithelium tear led to stretching forces along the posterior surface of the neurosensory retina with secondary foveal dehiscence. Conclusion Macular hole formation is one mechanism by which retinal pigment epithelium tears may cause vision loss in AMD.